A Review of Computer Vision Methods for Fruit Recognition. - Ian Kevin Witus; Chin Kim On; Rayner Alfred; Ag Asri Ag Ibrahim; Tan Tse Guan; Patricia Anthony (American Scientific Publishers, 2018)
This paper reviews the use of computer vision methodology in the field of fruit recognition. A fruit recognition process usually consists of three steps which are image acquisition, pre-processing, and image analysis. Various approaches are employed in the pre-processing and image analysis stages and some of these are presented in this paper. This review is conducted in order to understand the current state of the art of these approaches and to study the improvements and the advances in this area. A comparison between these methods will also be discussed.